ATR is a MYB regulated gene and potential therapeutic target in adenoid cystic carcinoma - Andersson, Mattias K. (Oncogenesis, 2020)
Adenoid cystic carcinoma (ACC) is a rare cancer that preferentially occurs in the head and neck, breast, as well as in other sites. It is an aggressive cancer with high rates of recurrence and distant metastasis. Patients with advanced disease are generally incurable due to the lack of effective systemic therapies. Activation of the master transcriptional regulator MYB is the genomic hallmark of ACC. MYB activation occurs through chromosomal translocation, copy number gain or enhancer hijacking, and is the key driving event in the pathogenesis of ACC. However, the functional consequences of alternative mechanisms of MYB activation are still uncertain. Here, we show that overexpression of MYB or MYB-NFIB fusions leads to transformation of human glandular epithelial cells in vitro and results in analogous cellular and molecular consequences. MYB and MYB-NFIB expression led to increased cell proliferation and upregulation of genes involved in cell cycle control, DNA replication, and DNA repair. Notably, we identified the DNA-damage sensor kinase ATR, as a MYB downstream therapeutic target that is overexpressed in primary ACCs and ACC patient-derived xenografts (PDXs). Treatment with the clinical ATR kinase inhibitor VX-970 induced apoptosis in MYB-positive ACC cells and growth inhibition in ACC PDXs. To our knowledge, ATR is the first example of an actionable target downstream of MYB that could be further exploited for therapeutic opportunities in ACC patients. Our findings may also have implications for other types of neoplasms with activation of the MYB oncogene.